Community Understanding and Local Practices of Infaq, Sadaqah and Waqf Management - Nora Putri; Tezi Asmadia; Rahmat Firdaus; Widi Nopiardo (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Infaq, sadaqah, and waqf are Islamic social finance instruments that have distinct legal characteristics and management mechanisms. However, in community-level practice, these three instruments are still often understood and managed in a uniform manner, which has the potential to cause inconsistencies in fund management, particularly with regard to waqf. The purpose of this study is to analyze the public’s understanding of infaq, sadaqah, and waqf; to examine the management of Islamic social funds; and to identify the factors that influence this understanding. This study employs a qualitative approach using a case study design. Primary data were collected through interviews with 10 active congregants, community leaders, and religious figures, and their validity was verified through source triangulation. Data analysis followed the Miles and Huberman model, which includes reduction, presentation, and drawing conclusions. The results of the study show that most informants still equate infaq, sadaqah, and waqf as forms of charity without understanding the differences in their legal principles and management. This perception is reinforced by fundraising and distribution practices that do not clearly distinguish between the various instruments, and is influenced by low levels of Islamic social financial literacy, limited education on muamalah fiqh, and strong local philanthropic traditions. The conclusions and implications of this study emphasize the importance of technical education on waqf contracts and the strengthening of management so that waqf can function productively in accordance with Sharia.